Optimization of Intracellular Polysaccharide Extraction Process and Analysis of Antioxidant Activity in Co-cultures of Sanghuangporus vaninii and Pleurotus sapidus - Yuantian LU; Di LIU (Shipin gongye ke-ji)
In this study, an ultrasonic synergistic semi-bionic method was explored to extract intracellular polysaccharides from Sanghuangporus vaninii and Pleurotus sapidus liquid co-cultures. By conducting single-factor experiments, Plackett-Burman design, and response surface design, the impact of 12 factors on co-culture intracellular polysaccharide (CC-IPS) extraction content, including extraction material-liquid ratios, extraction time, extraction temperature, and extraction solution pH were investigated. The antioxidant capacity of CC-IPS in vitro was evaluated by the DPPH and ABTS+ radical scavenging rates. Results showed that, the optimal extraction process parameters for the first, second, and third extractions, respectively, included material-to-liquid ratios of 1:17, 1:40, and 1:30 (g/mL), extraction times of 31, 30, and 30 min, extraction temperatures of 44, 40, and 50 ℃, and extraction solution pH levels of 3, 8, and 10. Under these optimal conditions, the CC-IPS extraction content was 86.4921±1.1924 mg/g, closed to the predicted value of 85.3981 mg/g. Additionally, the IC50 values of CC-IPS in the DPPH and ABTS+ free radical scavenging assays were determined to be 0.2425 and 0.1376 mg/mL, respectively. This study offers a theoretical foundation for the efficient utilization of intracellular polysaccharides in liquid fungal co-cultures.